How the learning of English is being influenced by the use of Information and Communication Technologies (ICTs) in students of B.A. Program of English as a foreign language in Colombian universities? (2015)
Figura 1.Frequency of benefits associated with the use of ICTs in ELT/Figure 2. Frequency of ICTs’ use in ELT/Annex. Prevalence of formation in ICTs in Colombian undergraduate teaching programs